Eksperimentasi TAPPS dan GI terhadap Pengetahuan dan Sikap Sosial Ditinjau dari Gaya Belajar - Ek Ajeng Rahmi Pinahayu; Nur Alamsyah; Risma Nurul Auliya; Luh Putu Widya Adnyani (Universitas Indraprasta PGRI Jakarta, 2021)
Education is faced with multi-dimensional problems, including the low competence of mathematical knowledge and the crisis of social aspects. This study aims to determine the difference in the effect of Thinking Aloud Pair Problem Solving (TAPPS), Group Investigation (GI), and Conventional models on knowledge competence and social attitudes in terms of learning styles. This is a quasi-experimental research, with a population of all eighth-grade students at SMP Negeri 24 Jakarta. Hypothesis testing used two-way multivariate analysis with unequal cells. The results of the research included: (1) TAPPS produced knowledge competence better than GI and conventional, and GI was better than conventional, (2) TAPPS and GI produced the same social attitudes, and both were better than conventional, (3) visual and auditorial resulted in the same good knowledge competence, and both were better than kinesthetic, (4) visual and auditory produced the same good social attitudes, and both were better than kinesthetic, (5) TAPPS and GI, knowledge competence of the three learning styles were equally good, whereas conventionally there were differences, (6) TAPPS and GI, social attitudes of the three types of learning styles were equally good, while conventionally there were differences, (7) in visual and auditory, knowledge competence of the three models were the same, while there were differences in kinesthetic, and (8) in visual and auditory, the social attitudes of the three models were the same, while there were differences in kinesthetic.